A method for changing the structure and performance of columnar crystal alloy film by irradiation and a method for preparing alloy film
By ion irradiating the CrMnFeCoNi high-entropy alloy film and changing its structure into an amorphous coated nanocrystal biphasic alloy, the problem of low strength of the columnar crystal structure is solved, the mechanical properties and radiation resistance are improved, and its application scope is expanded.
Patent Information
- Application Number
- CN202410751618.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-06-12
AI Technical Summary
The CrMnFeCoNi high-entropy alloy films prepared in the prior art generally have columnar crystal structures, and their strength is relatively low, which limits its application range.
By irradiating the columnar crystal alloy film at different doses, its structure is changed to an amorphous coated nanocrystalline biphasic alloy structure, thereby improving its mechanical properties and radiation resistance.
It significantly improves the hardness, tensile strength and yield strength of the alloy film, increases the radiation resistance, and expands its application range in multiple fields.
Smart Images

Figure CN118726880B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanocrystalline alloy film preparation, and in particular to a method for changing the structure and performance of a columnar crystal alloy film by irradiation and a preparation method thereof. Background Art
[0002] As a new type of alloy material, multi-principal element high entropy alloy (HEA) was first proposed by scholar Ye Junwei in 1995. It is composed of five or more main elements and the atomic percentage of each element is between 5-35%, so as to form high mixing entropy and achieve the purpose of preparing stable solid solution. The high entropy effect, lattice distortion effect, slow diffusion effect, etc. generated by the multi-principal element characteristics of the alloy make it easy for the alloy to form a simple solid solution structure (face-centered cubic, body-centered cubic or two-phase mixture) in structure, rather than a complex intermetallic compound, showing excellent fracture toughness, good ductility, radiation resistance, high temperature softening resistance and other excellent properties.
[0003] The fracture toughness of CrMnFeCoNi high entropy alloys is higher than that of all materials studied, and it is one of the most damage-resistant materials ever recorded. Moreover, the high yield strength and high fracture toughness of CrMnFeCoNi high entropy alloys show a wide temperature range, and even when the temperature drops below liquid nitrogen temperature, it still shows ultra-high toughness. Figure 1 As shown in the figure, when the temperature drops from 298K to 77K, the ultimate tensile strength and elongation of the CrMnFeCoNi high entropy alloy do not decrease sharply with the temperature drop like traditional alloys, but increase by 70% and 25% respectively, and the strength and elongation exceed 1GPa and 60% respectively at liquid nitrogen temperature. The high toughness at low temperature makes CrMnFeCoNi have a wider range of applications than most metal alloys, and it is expected to become a unique new material for engineering applications. However, the alloy films prepared by magnetron sputtering generally have a columnar crystal structure and generally have low strength, which limits the application of CrMnFeCoNi high entropy alloy films to a certain extent. Therefore, the preparation of CrMnFeCoNi high entropy alloy films with high strength is an urgent problem to be solved. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings, the present invention aims to provide a technical solution that can solve the above-mentioned problems.
[0005] A method for changing the structure and properties of a columnar crystal alloy film by irradiation comprises the following steps:
[0006] Preparation of columnar crystal alloy films;
[0007] The columnar crystal alloy film is subjected to ion irradiation of different doses, the structure of the alloy film after irradiation is observed, and its hardness is tested to obtain a relationship curve between the dose of ion irradiation and the changes in the structure and performance of the columnar crystal alloy film;
[0008] According to the relationship between ion irradiation and the changes in the structure and properties of the columnar crystal alloy film, the appropriate irradiation dose is determined to prepare an amorphous-coated nanocrystalline dual-phase alloy film that meets engineering requirements.
[0009] As a further solution of the present invention: the columnar crystal alloy film is a CrMnFeCoNi high entropy alloy film, and the columnar crystal alloy film is prepared by magnetron sputtering.
[0010] As a further solution of the present invention: the ions used in the ion irradiation are selected from He 2+ or He + Ion implantation experiments were carried out on columnar crystal alloy films using two ion sources at room temperature.
[0011] As a further embodiment of the present invention, the ion irradiation dose in the ion irradiation is 2×10 16 ions / cm 2 ~1×10 17 ions / cm.
[0012] As a further solution of the present invention, the ion implantation experiment in the ion irradiation is carried out under vacuum with Ar gas protection, wherein the vacuum degree is 1×10 -4 Pa~8×10 -5 Between Pa.
[0013] As a further solution of the present invention: the preparation of the columnar crystal alloy film specifically includes the following steps:
[0014] A CrMnFeCoNi high entropy alloy target with an equal atomic ratio is selected as a sputtering target, and the purity of the target is 99.9-99.99wt%;
[0015] The sputtering power source adopts a radio frequency power source, argon is used as the sputtering gas, a bias voltage of 60V-100V is added during the sputtering process, and an intermittent magnetron sputtering method is used to prepare a columnar crystal high entropy alloy film on a substrate.
[0016] As a further solution of the present invention: the power of the RF power supply during the sputtering process is 80W-120W, the duration of a single sputtering is 10min-20min, and the interval between two sputtering processes is 5min-10min.
[0017] As a further solution of the present invention: the purity of the argon gas used in the sputtering process is ≥99.999%, and the pressure in the sputtering chamber during the preparation process is 0.1Pa-1Pa.
[0018] As a further solution of the present invention: the thickness of the prepared columnar crystal high entropy alloy film is 500nm to 1500nm.
[0019] The present invention also provides a method for preparing an alloy film, comprising the following steps:
[0020] Cr with equal proportion of element content 20 Mn 20 Fe 20 Co 20 Ni 20 The target material is used as a sputtering target material, the purity of the target material is 99.9-99.99wt%, a radio frequency power supply is selected, the preparation power is 80W-120W, and a bias voltage of 60V-100V is added at the same time. The single sputtering preparation time is 10min-20min, and the cycle is 10-15 times, a total of 3-5 hours, and an interval of 5min-10min is taken between two sputtering processes, that is, a columnar crystal film with a thickness of about 500nm-1500nm is prepared;
[0021] The columnar crystal film was subjected to 2×10 16 ions / cm 2 ~1×10 17 ions / cm 2 Amorphous-coated nanocrystalline dual-phase alloy film was prepared by irradiating with a dose of He ions.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: the method of changing the structure and performance of columnar crystal alloy film based on irradiation properties of the present invention irradiates the columnar crystal alloy film by helium ions, changes the columnar crystal structure of the alloy film into an amorphous-coated nanocrystalline dual-phase alloy structure, not only improves the mechanical properties of the columnar crystal film, but also increases its radiation resistance. By controlling the size of the irradiation dose, the structure and performance of the columnar crystal alloy film can be adjusted, which is specifically manifested as follows: (i) Structural transformation and performance improvement: The present invention successfully transforms the columnar crystal alloy film into an amorphous-coated nanocrystalline dual-phase alloy structure through helium ion irradiation technology. This structural transformation significantly improves the mechanical properties of the alloy film, including hardness, tensile strength and yield strength, making it more suitable for various high-load engineering application scenarios. (ii) Enhanced radiation resistance: Since the amorphous-coated nanocrystalline dual-phase alloy structure has better structural stability and radiation resistance than the columnar crystal structure, the alloy film after irradiation treatment of the present invention has a broader application prospect in the fields requiring high radiation resistance such as nuclear industry and aerospace. (iii) High process controllability: The present invention can achieve fine adjustment of the structure and performance of the alloy film by precisely controlling the dose of ion irradiation. This highly controllable process feature enables the technical method of the present invention to customize alloy films with specific properties according to different application requirements. (iv) Expanded application scope of high entropy alloy films: The application scope of CrMnFeCoNi high entropy alloy films prepared by traditional magnetron sputtering is affected to a certain extent due to the limitation of columnar crystal structure; the present invention effectively overcomes this limitation by changing the microstructure of the film, further expanding the application scope of high entropy alloy films in multiple fields.
[0023] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0025] Figure 1 It is the stress-strain curve of CoCrFeMnNi high entropy alloy at different temperatures.
[0026] Figure 2 It is a schematic process flow diagram of a method for changing the structure and properties of a columnar crystal alloy film by irradiation according to an embodiment.
[0027] Figure 3 It is a schematic diagram of the process flow of a method for preparing an alloy film according to an embodiment.
[0028] Figure 4 These are TEM photos of high entropy alloy films before and after irradiation.
[0029] Figure 5 This is a schematic diagram comparing the hardness test results of high entropy alloy films before and after irradiation. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Embodiment 1
[0032] A method for changing the structure and performance of a columnar crystal alloy film by irradiation, wherein the columnar crystal structure of the alloy film is changed by irradiation to achieve the purpose of regulating strength; the method comprises the following steps:
[0033] Step S1, preparing a columnar crystal alloy film; the columnar crystal alloy film is a CrMnFeCoNi high entropy alloy film, the columnar crystal alloy film is prepared by magnetron sputtering, and a CrMnFeCoNi high entropy alloy target with an equiatomic ratio is selected as a sputtering target, and the purity of the target is 99.9-99.99wt%; the sputtering power supply adopts a radio frequency power supply, argon is used as a sputtering gas, a bias voltage of 60V-100V is applied during the sputtering process, and a columnar crystal high entropy alloy film is prepared on a substrate by an intermittent magnetron sputtering method. The power of the radio frequency power supply during the sputtering process is 80W-120W, the single sputtering time is 10min-20min, and the interval between the two sputtering processes is 5min-10min. The purity of the argon used in the sputtering process is ≥99.999%, and the pressure in the sputtering chamber during the preparation process is 0.1Pa-1Pa. The thickness of the prepared columnar crystal high entropy alloy film is 500nm~1500nm.
[0034] Step S2: subjecting the columnar crystal alloy film to ion irradiation at different doses, observing the structure of the alloy film after irradiation, and testing its hardness, and obtaining a relationship curve between the dose of ion irradiation and the changes in the structure and performance of the columnar crystal alloy film; the ions used in the ion irradiation are He 2+ or He + The ion implantation experiment of columnar alloy film was carried out at room temperature using two ion sources. The ion irradiation dose was 2×10 16 ions / cm 2~1×10 17 ions / cm 2 The ion implantation experiment in ion irradiation was carried out under vacuum with Ar gas protection, where the vacuum degree was 1×10 -4 Pa~8×10 -5 Between Pa;
[0035] Step S3: According to the relationship between ion irradiation and the change in structure and performance of the columnar crystal alloy film, determine the appropriate irradiation dose to prepare an amorphous-coated nanocrystalline dual-phase alloy film that meets engineering requirements.
[0036] Embodiment 2
[0037] A method for changing the structure and performance of a columnar crystal alloy film by irradiation, wherein the columnar crystal structure of the alloy film is changed by irradiation to achieve the purpose of regulating strength; the method comprises the following steps:
[0038] Step S1, preparing a columnar crystal alloy film; the columnar crystal alloy film is a CrMnFeCoNi high entropy alloy film, and the columnar crystal alloy film is prepared by magnetron sputtering, and an equiatomic ratio of CrMnFeCoNi high entropy alloy target is selected as the sputtering target, and the purity of the target is 99.9wt%; the sputtering power supply adopts a radio frequency power supply, argon is used as the sputtering gas, and a bias voltage of 60V is applied during the sputtering process. The columnar crystal high entropy alloy film is prepared on the substrate by an intermittent magnetron sputtering method. The power of the radio frequency power supply is 80W, the single sputtering time is 10min, and the interval between the two sputtering processes is 5min. The purity of the argon used in the sputtering process is ≥99.999%, and the pressure in the sputtering chamber during the preparation process is 0.1Pa. The thickness of the prepared columnar crystal high entropy alloy film is 500nm.
[0039] Step S2: subjecting the columnar crystal alloy film to ion irradiation at different doses, observing the structure of the alloy film after irradiation, and testing its hardness, and obtaining a relationship curve between the dose of ion irradiation and the changes in the structure and performance of the columnar crystal alloy film; the ions used in the ion irradiation are He 2+ or He + The ion implantation experiment of columnar alloy film was carried out at room temperature using two ion sources. The ion irradiation dose was 2×10 16 ions / cm 2 ~1×10 17 ions / cm 2 The ion implantation experiment in the ion irradiation was carried out in a vacuum protected by Ar gas, where the vacuum degree was 1×10 -4 Between Pa;
[0040] Step S3: According to the relationship between ion irradiation and the change in structure and performance of the columnar crystal alloy film, determine the appropriate irradiation dose to prepare an amorphous-coated nanocrystalline dual-phase alloy film that meets engineering requirements.
[0041] Embodiment 3
[0042] A method for changing the structure and performance of a columnar crystal alloy film by irradiation, wherein the columnar crystal structure of the alloy film is changed by irradiation to achieve the purpose of regulating strength; the method comprises the following steps:
[0043] Step S1: Preparation of columnar crystal alloy film: The columnar crystal alloy film is a CrMnFeCoNi high entropy alloy film, which is prepared by magnetron sputtering. A CrMnFeCoNi high entropy alloy target with an equiatomic ratio is selected as a sputtering target, and the purity of the target is 99.99wt%; the sputtering power supply adopts a radio frequency power supply, argon is used as a sputtering gas, and a bias voltage of 100V is applied during the sputtering process. The columnar crystal high entropy alloy film is prepared on the substrate by an intermittent magnetron sputtering method. The power of the radio frequency power supply is 120W, the single sputtering time is 20min, and the interval between the two sputtering processes is 10min. The purity of the argon used in the sputtering process is ≥99.999%, and the pressure in the sputtering chamber during the preparation process is 1Pa. The thickness of the prepared columnar crystal high entropy alloy film is 1500nm.
[0044] Step S2: subjecting the columnar crystal alloy film to ion irradiation at different doses, observing the structure of the alloy film after irradiation, and testing its hardness, and obtaining a relationship curve between the dose of ion irradiation and the changes in the structure and performance of the columnar crystal alloy film; the ions used in the ion irradiation are He 2+ or He + The ion implantation experiment of columnar alloy film was carried out at room temperature using two ion sources. The ion irradiation dose was 2×10 16 ions / cm 2 ~1×10 17 ions / cm 2 The ion implantation experiment in the ion irradiation was carried out in a vacuum protected by Ar gas, where the vacuum degree was 8×10 -5 Between Pa;
[0045] Step S3: According to the relationship between ion irradiation and the change in structure and performance of the columnar crystal alloy film, determine the appropriate irradiation dose to prepare an amorphous-coated nanocrystalline dual-phase alloy film that meets engineering requirements.
[0046] Embodiment 4
[0047] This embodiment provides a method for preparing an alloy film, which uses the radiation properties to change the structure and properties of the columnar crystal alloy film to achieve the purpose of improving the mechanical properties. The method includes the following steps:
[0048] Step S1: Cr with equal proportion of element content 20 Mn 20 Fe 20 Co 20 Ni 20 The target material is used as a sputtering target material, the purity of the target material is 99.9-99.99wt%, a radio frequency power supply is selected, the preparation power is 80W-120W, and a bias voltage of 60-100V is added at the same time. The single sputtering preparation time is 10min-20min, and the cycle is 10-15 times, a total of 3-5 hours. There is an interval of 5min-10min between two sputtering processes, and a columnar crystal film with a thickness of about 500nm~1500nm is prepared.
[0049] Step S2: 2×10 16 ions / cm 2 ~1×10 17 ions / cm 2 Dose of He ion irradiation, using He 2+ or He + Two ion sources were used for ion irradiation to prepare alloy films that met the requirements, and the structure and performance of the columnar crystal films after ion irradiation were tested.
[0050] It should be noted that in order to preliminarily identify the distribution of He ions and radiation damage along the depth direction after irradiation treatment, it is necessary to roughly calculate the irradiation process through SRIM before irradiation and select the appropriate irradiation dose.
[0051] Embodiment 5
[0052] This embodiment provides a method for preparing an alloy film, which uses the radiation properties to change the structure and properties of the columnar crystal alloy film to achieve the purpose of improving the mechanical properties. The method includes the following steps:
[0053] Step S1: Cr with equal proportion of element content 20 Mn 20 Fe 20 Co 20 Ni 20 The target material is used as a sputtering target material, and the purity of the target material is greater than 99.95wt%. A radio frequency power supply is selected, the preparation power is 120W, and the bias voltage is 80V. The single sputtering preparation time is 20min, and the cycle is repeated 12 times, a total of 4 hours, and there is a 5min break between two sputtering processes, so that a high entropy alloy film with a thickness of about 1000nm is prepared.
[0054] Step S2: 2×10 16 ions / cm 2 Dose of He ion irradiation, using He 2+ The ion source is used for ion irradiation to prepare alloy films that meet the requirements, and the structure and performance of the columnar crystal films after ion irradiation are tested.
[0055] Embodiment 6
[0056] This embodiment describes in detail how to use the technical solution of the present invention to prepare a high-strength CrMnFeCoNi high-entropy alloy film.
[0057] Step S1: Preparation of columnar crystal alloy film
[0058] 1. Select CrMnFeCoNi high entropy alloy target with equal atomic ratio as sputtering target to ensure that the purity of the target reaches 99.99wt%.
[0059] 2. The sputtering power source uses a radio frequency power source, and the sputtering power is set to 100 W. Argon is used as the sputtering gas, and the purity of argon reaches 99.999%.
[0060] 3. During the sputtering process, a bias voltage of 60 V was applied and the pressure in the sputtering chamber was controlled to 0.5 Pa.
[0061] 4. Sputtering was performed on the substrate using an intermittent magnetron sputtering method. The duration of a single sputtering was set to 15 minutes, with a 5-minute break after each sputtering, 12 cycles, and a total sputtering time of 3 hours.
[0062] 5. After the above steps, a columnar crystal high entropy alloy film with a thickness of about 1000nm was successfully prepared.
[0063] Step S2: Ion irradiation changes the film structure and properties
[0064] 1. Place the prepared columnar crystal alloy film in an ion irradiation device.
[0065] 2. Choose He 2+ Ions were used as the irradiation source and ion implantation experiments were carried out at room temperature.
[0066] 3. Control the dose of ion irradiation to 5×10 16 ions / cm 2 , ensure that the irradiation is carried out in a vacuum environment protected by Ar gas, and the vacuum degree is controlled at 5×10 -5 Pa.
[0067] 4. After irradiation, take out the film for structural and performance testing.
[0068] 5. After the above steps, the original columnar crystal structure was successfully transformed into an amorphous-coated nanocrystalline two-phase alloy structure, which significantly improved the mechanical properties and radiation resistance of the alloy film.
[0069] Embodiment 7
[0070] This embodiment provides another process for preparing a CrMnFeCoNi high entropy alloy film under irradiation dose.
[0071] Step S1 is the same as that in the sixth specific embodiment, and a columnar high entropy alloy film is successfully prepared.
[0072] During the ion irradiation process of step S2, the ion irradiation dose is controlled to be 8×10 16 ions / cm 2 , and the remaining conditions are the same as those in specific embodiment 6.
[0073] After the irradiation, the film was tested, and the results showed that under this irradiation dose, the structure and performance of the alloy film were also significantly improved, and the formation of the amorphous-coated nanocrystalline dual-phase alloy structure further improved the film's mechanical properties and radiation resistance. This proves that by adjusting the irradiation dose, the structure and performance of the alloy film can be finely controlled.
[0074] In summary, the technical solution of the present invention not only significantly improves the mechanical properties and radiation resistance of the alloy film, but also provides the possibility for customizing alloy films with specific properties through a highly controllable process, thereby greatly expanding the application prospects of high entropy alloy films.
[0075] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for changing the structure and properties of a columnar crystal alloy film by irradiation, characterized in that: The following steps are involved: a) preparing a columnar crystal alloy film, wherein the columnar crystal alloy film is a CrMnFeCoNi high entropy alloy film, and the columnar crystal alloy film is prepared by a magnetron sputtering method; b) subjecting the columnar crystal alloy film to ion irradiation of different doses, wherein the ion irradiation is performed at room temperature using a He²⁺ or He⁺ ion source, and the ion irradiation dose in the ion irradiation is 2×10 16 ions / cm 2 ~1×10 17 ions / cm 2 The ion implantation experiment was carried out under vacuum with Ar gas protection and the vacuum degree was 1×10⁻ 4 Pa~8×10⁻ 5 Between Pa; c) Observe the structure of the alloy film after irradiation, test its hardness, and obtain the relationship curve between the dose of ion irradiation and the changes in the structure and performance of the columnar crystal alloy film; d) According to the relationship between ion irradiation and the changes in the structure and properties of columnar crystal alloy films, the appropriate irradiation dose is determined to prepare an amorphous-coated nanocrystalline dual-phase structure alloy film that meets engineering requirements. The alloy film after ion irradiation shows an increase in hardness, tensile strength and yield strength, as well as an enhancement in radiation resistance.
2. The method of changing the structure and properties of a columnar crystal alloy film by irradiation according to claim 1, characterized in that: The preparation of the columnar crystal alloy film specifically includes the following steps: a) selecting a CrMnFeCoNi high entropy alloy target with an equal atomic ratio as a sputtering target, and the purity of the target is 99.9-99.99 wt%; b) The sputtering power source adopts a radio frequency power source, argon is used as the sputtering gas, a bias voltage of 60V-100V is applied during the sputtering process, and a columnar crystal high entropy alloy film is prepared on the substrate by an intermittent magnetron sputtering method; c) The power of the RF power supply during the sputtering process is 80W-120W, the duration of a single sputtering is 10min-20min, and the interval between two sputtering processes is 5min-10min; d) The purity of argon gas used in the sputtering process is ≥99.999 vol%, and the pressure in the sputtering chamber during the preparation process is 0.1 Pa-1 Pa; e) The thickness of the prepared columnar high entropy alloy film is 500nm~1500nm.
Citation Information
Patent Citations
Method for regulating and controlling creep property of nanocrystalline high-entropy alloy
CN113802101A